Analysis of the Effect of Celebrity Endorsement, Brand Image, and Product Quality on the Purchase Decision of Make Up Products with Purchase Intention as an Intervening Variable (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The beauty industry in Indonesia has been growing rapidly along with the increasing awareness among women of the importance of self-care and appearance. This condition encourages companies to compete through product innovation in order to meet diverse consumer preferences. This study aims to analyze the influence of celebrity endorsement, brand image, and product quality on purchasing decisions of Make Over products with purchase intention as an intervening variable. Primary data were collected through questionnaires from 200 respondents, using a non-probability sampling method with purposive sampling technique. Data analysis in this study was carried out using the Structural Equation Modelling (SEM) method based on Partial Least Square (PLS), with SMARTPLS 4.0 as the testing tool. The testing stages included: validity test (convergent validity, discriminant validity, average variance extracted), realibility test (cronbach’s alpha and composite reliability), R square, model fit, and hypothesis testing (path coefficient and specific indirect effect). The results of the study show that celebrity endorsement and product quality influence purchase intention of Make Over products, while brand image does not influence purchase intention. Celebrity endorsement does not influence purchasing decisions, whereas brand image and product quality do. Celebrity endorsement and product quality influence purchasing desicions through purchase intention as an intervening variable, while brand image does not influence purchasing decisions through purchase intention as an intervening variable.